Peran Pemasaran Digital dan Kreativitas dalam Membangun Minat Konsumen UMKM Berbasis Kearifan Lokal: Pendekatan PLS-SEM dan Kualitatif - Azwar Anas Idris, Andi; Pindasari, Nanang; Sukrin, Sukrin; Awaluddin, Awaluddin (LP3M, Universitas Muhammadiyah Kendari, 2026)
MSMEs in Kolaka Regency, such as Patowonua weaving and Tolaki Robusta coffee, play a strategic role in the economy and preservation of local wisdom. However, they face challenges of low digital literacy and communication creativity. This study aims to analyze the influence of digital marketing and creativity on consumer interest in order to formulate innovative marketing strategies based on local wisdom. The methods used are a quantitative survey of 75 consumers (analyzed with PLS-SEM) and qualitative interviews with MSME actors and experts. The results prove that digital marketing and creativity have a positive and significant effect on consumer interest. Strategies such as social media and creativity in products have proven effective in expanding market reach and building loyalty. The novelty of this research lies in the integration of a mixed method approach and the development of a strategy model that specifically combines digital marketing technology with creativity based on unique local potential, such as woven motifs and culinary specialties. The implications of this research are as a practical reference for MSME actors to adopt creative digital strategies, as well as a theoretical basis for the development of marketing literature that is contextual with local wisdom. The integration of these two things is the key to increasing the competitiveness of MSMEs.